2008
DOI: 10.1186/1752-1947-2-5
|View full text |Cite
|
Sign up to set email alerts
|

Choledochal cyst as a diagnostic pitfall: a case report

Abstract: Introduction: Choledochal cysts are rare congenital anomalies. Their diagnosis is difficult, particulary in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…The CECT review in referral hospital revealed type I choledochal cyst that was managed by Cholecystectomy with Cystectomy with Roux-en-Y hepaticojejunostomy. 16 There is another case report by Fransisca J. Siahaya et al of uncommon mixed type I and II choledochal cyst that was not taken care of during laparoscopic Cholecystectomy and subsequently needed second surgery after 02 months. 17 In the present case report, with the initial diagnosis of cholelithiasis with choledocholithiasis we performed Cholecystectomy with choledochotomy and retrieval of CBD stone followed by closure of choledochotomy over a T-tube.…”
Section: Discussionmentioning
confidence: 99%
“…The CECT review in referral hospital revealed type I choledochal cyst that was managed by Cholecystectomy with Cystectomy with Roux-en-Y hepaticojejunostomy. 16 There is another case report by Fransisca J. Siahaya et al of uncommon mixed type I and II choledochal cyst that was not taken care of during laparoscopic Cholecystectomy and subsequently needed second surgery after 02 months. 17 In the present case report, with the initial diagnosis of cholelithiasis with choledocholithiasis we performed Cholecystectomy with choledochotomy and retrieval of CBD stone followed by closure of choledochotomy over a T-tube.…”
Section: Discussionmentioning
confidence: 99%
“…And depending on cyst type (Todani type IV, V), further intervention may be necessary. Cholecystectomy is carried out due to the high risk of associated gall bladder malignancy [17].Likewise among all patients we operated complete cyst excision with cholecystectomy followed by biliary reconstruction using Roux-en-Y hepaticojejunostomy was performed. We recommend the same as the main stay of treatment for choledochal cyst Type I and Type IV.…”
Section: Discussionmentioning
confidence: 99%
“…22 Other imaging modalities like Endoscopic Retrograde Cholangiopancreatography (ERCP) or MRCP can precisely visualize the extra hepatic bile duct. 9 MRCP has been advocated as the ideal and non-invasive complete diagnostic modality for choledochal cyst as it ensures accurate visualization of the entire pancreatobiliary system. 21,23 These investigations could not be done in any of the patients due to lack of these facilities at our center at that time.…”
Section: Jcms Nepal 2017;13(1):174-8 Choledochal Cyst: Clinical Presementioning
confidence: 99%
“…Ultrasonography (USG) is usually the first examination and is a very sensitive (71 to 97%) in the detection of choledochal cyst. 9,18 A properly performed high resolution USG is the best screening test. 20 Le et al 21 described 38 cases of choledochal cyst where in all cases USG was the only diagnostic modality.…”
Section: Original Research Articlementioning
confidence: 99%
See 1 more Smart Citation